Teologiczne skutki pychy władców i narodów w Biblii greckiej - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2011)
The article argues that anyone who sins with any of the attitudes denoted by the verb hypsoō w will not evade adequate punishment. When an individual commits this sin the punishment is loss of the ability to rule, illness or even death. If nations succumb to pride their fate is destruction as punishment for impenitence and disobedience to God. Punishment is inflicted on heathen rulers and nations as well as on the kings and the chosen people. Then God is the ultimate punishing instance and the foundation of justice. In turn the attitude of those who bravely oppose the pride of the rulers and whole communities encourages others to persevere in the conduct that pleases God.